Assessment of urban overheating mitigation strategies in a square in Rome, Italy. (1st March 2019) - Battista, Gabriele; de Lieto Vollaro, Roberto; Zinzi, Michele
Highlights: Numerical model thought ENVI-met of a densely populated Rome district has been developed. The effects of urban vegetation improvement, the use of cool pavements, the use of a canopy and the use of water stretch were analysed. Experimental data, such as the air temperature and the relative humidity, have been collected in order to set up the boundary conditions and to calibrate the numerical model. Time variation of outdoor thermal comfort thought the UTCI has been estimated. Thermal comfort improvement is less sensitive to the implemented solutions than the air temperature analysis. Abstract: Climate changes and urbanization are the main causes of the urban heat island. Defined as the air temperature rising in the urban areas despite of the rural ones, it amplifies the global warming phenomenon. The absence of green areas, open water and free unsurfaced spaces creates a sort of urban cap and a heat reflection effect, from the bottom upwards, which persists in the early hours of the night. This paper aims to investigate different technical solutions to mitigate the microclimatic conditions and to improve the thermal comfort of the citizens of a densely populated Roman area: Mirti square in the Centocelle district. This area is a good describer of the local urban heat island, because it shows a high density of buildings, a lack of vegetation and an absence of water sources like fountains. So, this area has a high thermal stress and the high presence of people raises the benefits of the mitigation techniques chosen for Mirti square. A numerical model was developed thought ENVI-met in order to assess the effects of the mitigation techniques in terms of air temperature decrease. The main techniques considered are the implementation of the urban vegetation, the use of cool pavements, the use of a canopy and the use of water stretch. Experimental data such as air temperature and relative humidity were collected in order to set up the boundary conditions and to calibrate the numerical model.